Fundamental of Entrepreneurship (ENT 300) Usaha Jaya Enterprise / Joseph Pairin Puloh...[et al.] - Puloh, Joseph Pail·in; Yunus, Nur Zahirah Syafiqah; Bojeng, Mohd Zulkarnain; Gusin, Mhd Sahdan (2019)
Usaha Jaya Enterprise is a form 0 f business partnership, which consists 0 f 4 members. Under partnership agreement, we have agreed to appoint Joseph Pairin Puloh as a general manager and administrative manager, Nur Zahirah Syafiqah binti Yunus as a marketing manager, Mohd Zulkarnain bin Bojeng as operational manager and Mhd Sahdan bin Gusin as our financial manager. We are also agreed to contribute an amount of RM 240,000 as our capital. Our location is 2nd Floor Storeys Shoplot @ Jln Satok/Kulas, Kuching, Sarawak. Our marketing strategies are targeting all people that need canopy for doing an event. Usaha Jaya Enterprise is the business that provide a canopy rental for any event such as wedding, launching, road show, ceremony and other event. We also provide a decoration service for the canopy such as scallop, clothing, legging, table cloth, and chair cloth.